INOVASI PEMBELAJARAN GEOMETRI SEKOLAH DASAR MELALUI POP-UP BOOK ETNOMATEMATIKA BANGUNAN MASJID AL-AKBAR SURABAYA - Hamidah, Winda; Feny Rita Fiantika; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the lack of interest of students in implementing mathematics learning activities. Mathematics learning will be more interesting if you use media. The media used is an ethnomathematics-based popup book media which displays three- dimensional elements by increasing understanding of geometric concepts and connecting them with the local culture of the Surabaya Al-Akbar Mosque on the geometric material of cubes and blocks. The aim of this research is to describe observations of teacher activities, student responses and student learning outcomes for class VI students at SDN Margorejo 1 Surabaya. This research is descriptive quantitative research. Data in the form of observations of teacher activities, student responses and student learning outcomes. The results of the research show that observations of teacher activities are in the "good" category, student responses are in the "very good" category and student learning outcomes are in the "very good" category.